NOS1 inhibits the interferon response of cancer cells by S-nitrosylation of HDAC2 - Xu, Pengfei (J Exp Clin Cancer Res, 2019)
BACKGROUND: The dysfunction of type I interferon (IFN) signaling is an important mechanism of immune escape and metastasis in tumors. Increased NOS1 expression has been detected in melanoma, which correlated with dysfunctional IFN signaling and poor response to immunotherapy, but the specific mechanism has not been determined. In this study, we investigated the regulation of NOS1 on the interferon response and clarified the relevant molecular mechanisms. METHODS: After stable transfection of A375 cells with NOS1 expression plasmids, the transcription and expression of IFNα-stimulated genes (ISGs) were assessed using pISRE luciferase reporter gene analysis, RT-PCR, and western blotting, respectively. The effect of NOS1 on lung metastasis was assessed in melanoma mouse models. A biotin-switch assay was performed to detect the S-nitrosylation of HDAC2 by NOS1. ChIP-qPCR was conducted to measure the binding of HDAC2, H4K16ac, H4K5ac, H3ac, and RNA polymerase II in the promoters of ISGs after IFNα stimulation. This effect was further evaluated by altering the expression level of HDAC2 or by transfecting the HDAC2-C262A/C274A site mutant plasmids into cells. The coimmunoprecipitation assay was performed to detect the interaction of HDAC2 with STAT1 and STAT2. Loss-of-function and gain-of-function approaches were used to examine the effect of HDAC2-C262A/C274A on lung metastasis. Tumor infiltrating lymphocytes were analyzed by flow cytometry. RESULTS: HDAC2 is recruited to the promoter of ISGs and deacetylates H4K16 for the optimal expression of ISGs in response to IFNα treatment. Overexpression of NOS1 in melanoma cells decreases IFNα-responsiveness and induces the S-nitrosylation of HDAC2-C262/C274. This modification decreases the binding of HDAC2 with STAT1, thereby reducing the recruitment of HDAC2 to the ISG promoter and the deacetylation of H4K16. Moreover, expression of a mutant form of HDAC2, which cannot be nitrosylated, reverses the inhibition of ISG expression by NOS1 in vitro and decreases NOS1-induced lung metastasis and inhibition of tumor infiltrating lymphocytes in a melanoma mouse model. CONCLUSIONS: This study provides evidence that NOS1 induces dysfunctional IFN signaling to promote lung metastasis in melanoma, highlighting NOS1-induced S-nitrosylation of HDAC2 in the regulation of IFN signaling via histone modification.